Метрологічні завдання аерофотозйомки за допомогою безпілотних літальних апаратів - Микийчук, М. М.; Марків, В. І.; Mykyichuk, M. M.; Markiv, V. I. (Видавництво Львівської політехніки, 2017)
Розглянуто використання безпілотних літальних апаратів для потреб аерофотозйомки місцевості. Встановлено, що використання пощирених навігаційних систем може спричиняти похибки в умовах з певними перешкодами, зокрема в містах з густою забудовою. Саме тому запропоновано визначати координати безпілотних літальних апаратів з урахуванням похибок системи глобального позиціонування. Позиціонування безпілотників розглянуто з урахуванням розташування наземних об’єктів та роз- робленої моделі навколишнього середовища. Розглянуто оцінку координат безпілотників з використанням додаткової інформа- ції з бортової системи нагляду. В цьому контексті важливою є автоматизована обробка аерофотознімків. Використано методику чотирипроцесорного векторного обчислення. Для обробки даних, що відповідають за позиціонування, використано коефіцієнт Калмана–Бьюсі.

This paper dwells upon the use of remote-piloted vehicles in the airphotoshooting of different areas. There is a need to process images automatically, for example, by searching the overlapping areas for stitching of the images. Air monitoring by using images can make qualitative changes in monitoring of the terrain, help prevent late decisions due to insufficient information base or data collection for expert analysis. In this context, it is highlighted that the positioning of remote-piloted vehicles plays vital role. Nowadays GNSS (Global Satellite Navigation System) and GPS (Global Positioning System) systems are widely used by using additional information from on-board system. It is highlighted to make positioning of remote-piloted vehicle based on the analysis of the location of the ground objects and the previously developed model of the environment. For this purpose, it is necessary to develop method of airphotoshooting by using of on-board 4-processor vector calculator that provides processing of photographs. This computational core also provides automatic flight in the absence of reception of GNSS data, being guided by the indications of the inertial block, which includes a combination of accelerometers and gyroscopes. To process data from sensors responsible for positioning, the iterative formula was used, so called, Kalman-Bucy coefficient.
Metrology tasks of airphotoshooting by remote-piloted vehicle
Keywords: безпілотний літальний апарат; аерофотознімання; позиціонування безпілотних літальних апаратів; зшивання зображень; локальна навігація; зовнішні і внутрішні сенсори; remote-piloted vehicle; airphotoshooting; remote-piloted vehicle positioning; image stitching; local navigation; external and internal sensors; 621.317.08